2005
DOI: 10.1042/cs20040191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a dual endothelin-1 receptor antagonist on airway obstruction and acute lung injury in sheep following smoke inhalation and burn injury

Abstract: Studies have suggested that ET-1 (endothelin-1) is associated with lung injury, airway inflammation and increased vascular permeability. In the present study we have tested the hypothesis that treatment with a dual ET-1 receptor antagonist will decrease airway obstruction and improve pulmonary function in sheep with combined S+B (smoke inhalation and burn) injury. Twelve sheep received S+B injury using the following protocol: six sheep were treated with tezosentan, an ETA and ETB receptor antagonist, and six s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Similarly, Cox et al. [44] found that tezosentan does not provide clear protection against ALI that was induced by smoke inhalation or burns in sheep. This suggests that the timing of intervention is important in dynamic progressive processes such as ALI.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Cox et al. [44] found that tezosentan does not provide clear protection against ALI that was induced by smoke inhalation or burns in sheep. This suggests that the timing of intervention is important in dynamic progressive processes such as ALI.…”
Section: Discussionmentioning
confidence: 98%
“…ET-1 increases pulmonary microvascular pressure, causing edema formation, and several studies have suggested that ET-1 receptor inhibition has a protective effect in models of acute lung injury (12,(38)(39)(40). ET-1 is a potent vasoactive peptide released by endothelial and epithelial cells during stimuli such as shear stress, hypoxia, and inflammation (11,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…24 Typically, in the ovine model of inhalation injury, arterial oxygen tension begins to decrease between 12 and 24 hours after injury, and virtually all animals are receiving 100% oxygen at 48 hours after injury. 25 Sham animals received instrumentation and anesthesia without burn or inhalation injury and were studied for 48 hours. Fluid resuscitation in the sham animals was 2 ml/kg/hr.…”
Section: Methodsmentioning
confidence: 99%